Transcranial Direct Current Stimulation Does Not Improve Countermovement Jump Performance in Young Healthy Men. Issue 10 (October 2021) - Romero-Arenas, Salvador; Calderón-Nadal, Giancarlo; Alix-Fages, Carlos; Jerez-Martínez, Agustín; Colomer-Poveda, David; Márquez, Gonzalo
Abstract : Abstract: Romero-Arenas, S, Calderón-Nadal, G, Alix-Fages, C, Jerez-Martínez, A, Colomer-Poveda, D, and Márquez, G. Transcranial direct current stimulation does not improve countermovement jump performance in young healthy men. J Strength Cond Res 35(10): 2918–2921, 2021—The main purpose of this study was to report the effects of transcranial direct current stimulation (tDCS) on countermovement jump (CMJ) performance in young healthy men. Seventeen healthy male subjects volunteered for the study (age: 22.4 ± 2.6 years; body mass: 71.8 ± 8.7 kg; height: 174.6 ± 5.9 cm; and CMJ height: 36.8 ± 6.3 cm). After a familiarization session, subjects underwent 3 experimental conditions, 7 days apart, in a randomized, double-blinded crossover design: anodal, cathodal, and sham tDCS. The stimulation was applied over the dorsolateral prefrontal cortex for 15 minutes. During experimental sessions, subjects completed a warm-up and 3 CMJ trials separated by 1 minute before and after each of the 3 experimental conditions. Countermovement jump height and muscular peak power were extracted from the best CMJ in each moment. A 2-way repeated-measures analysis of variance with time and condition as factors were performed for CMJ height and muscular peak power. Effect size analysis was conducted using Cohen's d coefficient. The analysis did not show either significant main effects or interactions for both time and condition factors in the CMJ performance ( p > 0.05). Furthermore, effect size was trivial for all conditions ( d : 0.01–0.14) in CMJ height and muscular peak power. These findings suggest that tDCS may not be a valuable tool to improve vertical jump performance.